2002
DOI: 10.1523/jneurosci.22-03-01171.2002
|View full text |Cite
|
Sign up to set email alerts
|

Competition between Memory Systems: Acetylcholine Release in the Hippocampus Correlates Negatively with Good Performance on an Amygdala-Dependent Task

Abstract: Lesions of the amygdala impair acquisition of a food conditioned place preference (CPP) task. In contrast, lesions of the fornix facilitate acquisition on this task, showing that an intact hippocampal system can interfere with learning an amygdaladependent task. Our recent findings indicate that acetylcholine (ACh) release in the hippocampus increases while rats perform a hippocampus-dependent spontaneous alternation task. To the extent that ACh output in the hippocampus reflects activation of that brain area … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
62
2

Year Published

2003
2003
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(71 citation statements)
references
References 45 publications
(47 reference statements)
7
62
2
Order By: Relevance
“…These findings are thus in accordance with the current view supporting a role for ACh in regulating the relative contribution of different neural systems to learning (Marighetto et al, 1993;McIntyre et al, 2002;Gold, 2003;Parent and Baxter, 2004;Pych et al, 2005). It has been shown that a high level of ACh release in the hippocampus was associated with poor memory for the amygdala-dependent conditioned cue preference task (McIntyre et al, 2002) and, more generally, that the hippocampal-dependent processing of contextual information can interfere with the acquisition of this amygdala-dependent learning task (White and McDonald, 2002). Although in keeping with these previous findings, our present study further reveals that elevated levels of the hippocampal ACh not only favor the formation of a context-US association but also impede formation of an amygdala-based simple toneshock association.…”
Section: Hippocampal Ach Controls Amygdalar Functionsupporting
confidence: 92%
See 1 more Smart Citation
“…These findings are thus in accordance with the current view supporting a role for ACh in regulating the relative contribution of different neural systems to learning (Marighetto et al, 1993;McIntyre et al, 2002;Gold, 2003;Parent and Baxter, 2004;Pych et al, 2005). It has been shown that a high level of ACh release in the hippocampus was associated with poor memory for the amygdala-dependent conditioned cue preference task (McIntyre et al, 2002) and, more generally, that the hippocampal-dependent processing of contextual information can interfere with the acquisition of this amygdala-dependent learning task (White and McDonald, 2002). Although in keeping with these previous findings, our present study further reveals that elevated levels of the hippocampal ACh not only favor the formation of a context-US association but also impede formation of an amygdala-based simple toneshock association.…”
Section: Hippocampal Ach Controls Amygdalar Functionsupporting
confidence: 92%
“…It follows that the LA/BLA pattern of p-ERK1/2 in physostigmine-infused mice mimics that observed in controls trained with the unpairing procedure (i.e., predominant contextual conditioning, similar p-ERK1/2 levels in LA and BLA). These findings are thus in accordance with the current view supporting a role for ACh in regulating the relative contribution of different neural systems to learning (Marighetto et al, 1993;McIntyre et al, 2002;Gold, 2003;Parent and Baxter, 2004;Pych et al, 2005). It has been shown that a high level of ACh release in the hippocampus was associated with poor memory for the amygdala-dependent conditioned cue preference task (McIntyre et al, 2002) and, more generally, that the hippocampal-dependent processing of contextual information can interfere with the acquisition of this amygdala-dependent learning task (White and McDonald, 2002).…”
Section: Hippocampal Ach Controls Amygdalar Functionsupporting
confidence: 91%
“…Thus, damage to the In the current experiment we examined whether thiamine deficiency, which causes diencephalic pathology, alters both hippocampal and amygdalar ACh efflux when rats are actively exploring a maze. Measurement of ACh efflux in the brains of rats during learning appears to be a useful marker of activation of a given neural system-particularly the hippocampus and amygdala [8,14,31,32,33]. We chose a task, spontaneous alternation, which is sensitive to diencephalic damage [25] and to changes in release of ACh in both the hippocampus and amygdala [8,31,34].…”
Section: Nih Public Accessmentioning
confidence: 99%
“…Measurement of ACh efflux in the brains of rats during learning appears to be a useful marker of activation of a given neural system-particularly the hippocampus and amygdala [8,14,31,32,33]. We chose a task, spontaneous alternation, which is sensitive to diencephalic damage [25] and to changes in release of ACh in both the hippocampus and amygdala [8,31,34]. In addition, to understand the neuroanatomical correlates of this dysfunction we used unbiased stereological techniques to estimate ChAT cell populations in the MS/DB (that projects to the hippocampus) as wells as the nucleus basalis of Meynert (NBM; that projects to the amygdala).…”
mentioning
confidence: 99%
“…There is a dramatic rise in hippocampal ACh while rats are transversing a T-maze or a radial arm maze-that in some instances is related to the degree of learning (Fadda, Cocco, & Stancampiano, 2000;Fadda, Melis, & Stancampiano, 1996). In addition to the hippocampus, ACh efflux in the striatum and amygdala can also be used to assess amount of neural activation during maze learning (Chang & Gold, 2003a;McIntyre, Marriott, & Gold, 2003;McIntyre, Pal, Marriott, & Gold, 2002;Stancampiano, Cocco, Cugusi, Sarais, & Fadda, 1999). ACh release in the hippocampus and striatum predicts which system and thus which strategy (place or response) a given rat will use to solve a T-maze discrimination task (Chang & Gold, 2003a;McIntyre et al, 2003).…”
Section: Introductionmentioning
confidence: 99%